Preclinical and Clinical Therapeutic Strategies Affecting Tumor-Associated Macrophages in Hepatocellular Carcinoma. (16th October 2018) - Degroote, H.; Van Dierendonck, A.; Geerts, A.; Van Vlierberghe, H.; Devisscher, L.
Abstract : Hepatocellular carcinoma (HCC) most often develops in patients with underlying liver disease characterized by chronic nonresolving inflammation. Tumor-associated macrophages (TAMs) are one of the most abundant immune cell populations within the tumoral microenvironment. As key actors of cancer-related inflammation, they promote tumor growth by suppression of effective anticancer immunity, stimulation of angiogenesis, and tissue remodeling. Therefore, they have become an attractive and promising target for immunotherapy. The heterogeneity of TAM subtypes and their origin and dynamic phenotype during the initiation and progression of HCC has been partially unraveled and forms the base for the development of therapeutic agents. Current approaches are aimed at decreasing the population of TAMs by depleting macrophages present in the tumor, blocking the recruitment of bone marrow-derived monocytes, and/or functionally reprogramming TAMs to antitumoral behavior. In this review, the preclinical evolution and hitherto clinical trials for TAM-targeted therapy in HCC will be highlighted.